Easy or Not—The Advances of EZH2 in Regulating T Cell Development, Differentiation, and Activation in Antitumor Immunity - Huang, Jiaqi; Zhang, Jie; Guo, Zhengyang; Li, Chen; Tan, Zhen; Wang, Junjie; Yang, Jianling; Xue, Lixiang (Frontiers in Immunology, 2021)
Enhancer of zeste homolog 2 (EZH2) is the catalytic subunit of polycomb repressive complex 2 (PRC2), which regulates downstream gene expression by trimethylation of lysine 27 in histone H3 (H3K27me3). EZH2 mutations or overexpressions are associated with many types of cancer. As inhibition of EZH2 activity could upregulate the expression of tumor suppressor genes, EZH2 has recently become an interesting therapeutic target for cancer therapy. Moreover, accumulating evidence has shown that EZH2 may contribute to the regulation of immune cells, especially T cells. EZH2 regulates T cell development, differentiation, and function, suggesting that EZH2 also regulates immune homeostasis in addition to tumor suppressor genes. Moreover, EZH2 can regulate T cell fate by targeting non-T cell factors such as metabolism, cytokines, and myeloid-derived suppressor cells. The role of EZH2 in this process has not been fully addressed. This review discusses up-to-date research on EZH2-mediated regulation of immunological function and the progress of immunological therapeutic strategies based on this regulation.